E-021 Initial experience using the Penumbra Coil 400: comparison of aneurysm packing and coil efficiency. (4th July 2012) - Milburn, J; Pansara, A; Martinez, R; Vidal, G
Abstract : Introduction: Penumbra Coil 400 gained FDA approval and was introduced to the market April 2011. Due to its larger 0.020″ diameter and inherent softness, there is potential to provide more efficient coiling. More efficient coiling may result in shorter catheter in vessel time and less radiation exposure for the patient and healthcare team. This is a retrospective single operator experience of aneurysm coiling at the Ochsner Clinic comparing the Penumbra Coil 400 with the other most commonly used coil types, Orbit and Galaxy. Methods: Forty aneurysms treated exclusively with Orbit or Galaxy coils and 18 aneurysms treated only with Penumbra coils from 2010 to February 2012 were compared. There were 36 other aneurysm treatments excluded because they were not initial treatments, other manufacturers' coils were used, or they had mixed coil types. Measurements included packing density, number of coils per unit aneurysm volume, and total coil length per unit aneurysm volume. Other parameters including presenting aneurysm rupture status, frequency of stent or balloon use, aneurysm occlusion rates, and complications were also compared. Results: Mean packing density of 33.7% using Penumbra coils was significantly >24.4% for Orbit/Galaxy coils (p=0.0001). Number of coils per aneurysm volume of 0.026 coils/mm 3 for Penumbra was significantly lower than 0.114 coils/mm 3 for Orbit/Galaxy (p<0.001). Total coil length per aneurysm volume of 0.11 cm/mm 3 for Penumbra was significantly <0.32 cm/mm 3 for Orbit/Galaxy treatments (p<0.001). Aneurysm sizes ranged from 6.3 mm 3 to 5564.0 mm 3 in the Orbit/Galaxy group and from 31.0 mm 3 to 12 666.4 mm 3 in the Penumbra group. There were more ruptured aneurysms treated using Orbit/Galaxy (67%) than with Penumbra (28%). Aneurysm occlusion rates and frequency of balloons or stent use was similar in both groups. There were no procedural complications in the Penumbra cases, and there were two small branch infarctions in the Orbit/Galaxy group that were not clinically apparent. Conclusion: In our practice, aneurysm treatments with the Penumbra 400 coil have resulted in significantly greater average packing density using less than one fourth of the number of coils per volume compared with Orbit/Galaxy. Aneurysms were larger in the penumbra group, and more ruptured aneurysms were treated with Orbit/Galaxy. Occlusion rates and complication rates were similar and acceptable in both groups. Competing interests: J Milburn: Penumbra. A Pansara: None. R Martinez: None. G Vidal: None.